Improved Detection of Target Metabolites in Brain Tumors with Intermediate TE, High SNR, and High Bandwidth Spin-Echo Sequence at 5T - Sun, Wenbo; Xu, Dan; Yang, YanXing; Wen, Linfei; Yu, Hanjiang; Xing, Yaowen; Song, Xiaopeng; Li, Huan; Xu, Haibo (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Due to high chemical shift displacement, challenges emerge at ultra-high fields when measuring metabolites using 1H-MRS. Our goal was to investigate how well the high SNR and high bandwidth spin-echo (HISE) technique perform at 5T for detecting target metabolites in brain tumors.MATERIALS AND METHODS: Twenty-six subjects suspected of having brain tumors were enrolled. HISE and point-resolved spectroscopy (PRESS) single-voxel spectroscopy scans were collected with a 5T clinical scanner with an intermediate TE (TE = 144 ms). The main metabolites, including total NAA, Cr, and total Cho, were accessed and compared between HISE and PRESS using a paired Student t test, with full width at half maximum and SNR as covariates. The detection rate of specific metabolites, including lactate, alanine, and lipid, and subjective spectral quality were accessed and compared between HISE and PRESS.RESULTS: Twenty-three pathologically confirmed brain tumors were included. Only the full width at half maximum for total NAA was significantly lower with HISE than with PRESS (P < .05). HISE showed a significantly higher SNR for total NAA, Cr, and total Cho compared with PRESS (P < .05). Lactate was detected in 21 of the 23 cases using HISE, but in only 4 cases using PRESS. HISE detected alanine in 8 of 9 meningiomas, whereas PRESS detected alanine in just 3 meningiomas. PRESS found lipid in more cases than HISE, while HISE outperformed PRESS in terms of subjective spectral quality.CONCLUSIONS: HISE outperformed the clinical standard PRESS technique in detecting target metabolites of brain tumors at 5T, particularly lactate and alanine.AlaalanineCSDEchemical shift displacement errorFWHMfull width at half maximum2-HG2-hydroxyglutarateHISEhigh bandwidth spin-echoLaclactateLiplipidPRESSpoint-resolved spectroscopyRFradiofrequencySTEAMstimulated echo acquisition modeSVSsingle-voxel spectroscopyttotal